Equity valuation of Ibersol SGPS, SA - Castilho, Maria Inês Paiva (2021)
The aim of the present project is to make a reliable valuation of a listed company with the purpose of providing essential information for potential investors and achieving the target price of the company’s shares as of 31st December of 2019. The company chosen was Ibersol SGPS, S.A., that is a multi-brand group operating in the food service sector. The spread of COVID-19, declared by the World Health Organization as a global pandemic in 2020, deeply impacted the world economy and consumers’ habits. Therefore, the pandemic effect is also considered in this project. Between the models chosen to perform the valuation (DFC, Relative Valuation and EVA), the most accurate one is DFC as all the forecasts were produced considering the pandemic impact in the food service sector. At the end of the valuation, the result obtained was 5.80€, which would suggest a sell recommendation as the market reference value at 31 of December of 2019 was 8.00€. However, investors’ decision should also contemplate the speed of largescale vaccination and the good prospects of some sectors where Ibersol operates, such as delivery, take-away and drive services. Moreover, at the date of the end of this project, the company’ share price was around 5.76€, which suggests that the forecasts made in this project are in line with the current situation of Ibersol. Thus, the final recommendation for investors might change to from a Sell to a Hold.